Android application for extractive text summarization. Issue 5 (16th August 2021) - Hardiyanto, Ayi; Fitrianah, Devi
Abstract : Purpose: The purpose of this study is to provide an automatic text summarization experience using the extractive method within an application implemented on Android. Design/methodology/approach: Scrum framework is used to keep pace with trends and enhance the development process of this application. The code implementation using Flutter Software Development Kit in client-side and Python with Flask on server-side is aimed to have better integration and maintenance process. The authors had done black-box testing and white-box testing to ensure the application runs as expected for both the behavior and code. Findings: This application will provide full functionality to perform the summarization process, starting from the input to the presentation of the results of text summarization. Originality/value: Besides summarizing text, the application is also capable of copying and saving the result into the device.